Research on Power Grid Project Cost and Management Evaluation Method - Xiaorui, Li; Bing, Gu (International Conference on Measuring Technology and Mechatronics Automation (Print), 2021)
In view of the problem that the cable joint looseness or other mechanical abnormalities in the high-voltage distribution cabinet is difficult to predict in time, through this project, the corresponding relationship between the comprehensive information sensing data in the high-voltage distribution cabinet and the mechanical strength weakening of the cable joint is studied, and the early warning method of joint looseness is established to improve the operation reliability of the distribution cableIn order to deeply study the characteristics of loose electrical connection fault of bolted cable and realize effective fault identification, taking bolted cable joint as the research object, the loose fault test under different loose degree and different current conditions was carried out by using cable joint loosening fault test platform. Based on the principle of fuzzy structural element, according to the influence factors of current, power factor and vibration state of cable joint, the structural element expression of fuzzy comprehensive evaluation is given, and the loose fault of bolted cable joint is comprehensively evaluated. The results show that the method can effectively identify the loose state of bolted cable joint, and provide theoretical basis for detection and protection of loose fault.